Kualitas Hidup Pasien Lansia Pengguna Gigi Tiruan Lepasan Di Klinik Terpadu RSGM Universitas Kristen Maranatha - Feby Rahmadiatul Asvi; Silvia Naliani; Shelly Lelyana (SONDE (Sound of Dentistry), 2023)
Older people tend to have a high prevalence of tooth loss due to age factors and dental and oral diseases. To overcome this, the elderly use dentures to restore masticatory and speech functions, improve aesthetics, and maintain the health of existing oral tissue, thereby preventing further damage. This condition determines the quality of life of elderly patients. So, this research aims to determine the effect of using dentures on the quality of life of the elderly at the integrated clinic RSGM Maranatha Christian University. Measuring the quality of life of elderly patients who use dentures using the Geriatric Oral Health Assessment Index (GOHAI) instrument, which consists of 12 questions covering the dimensions of physical function, psycho-social function, and pain or discomfort. The research results show that most older people have a quality of life in the good category. The quality-of-life dimension based on the GOHAI instrument shows that most respondents admitted that the physical function dimension related to the use of dentures tends to cause their quality of life to be good. One of the statements with the most value in respondents' opinions is about limiting the types of food that can be eaten.